Quasi-solid-state quantum dot sensitized solar cells with power conversion efficiency over 9% and high stability. Issue 38 (15th September 2016) - Feng, Wenliang; Zhao, Leilei; Du, Jun; Li, Yan; Zhong, Xinhua
Abstract : A highly conductive gel electrolyte based on sodium carboxymethylcellulose was developed to construct quasi-solid-state quantum dot sensitized solar cells that exhibit power conversion efficiency over 9% and a significant improvement in stability compared to liquid-junction QDSCs. Abstract : Although the highest power conversion efficiency (PCE) of quantum dot sensitized solar cells (QDSCs) has been continuously updated recently, the stability limited by the volatilization and the leakage of liquid electrolytes remain main challenges for the application of QDSCs. To construct a quasi-solid-state QDSC, a new gel electrolyte was developed by solidifying a polysulfide aqueous solution using sodium carboxymethylcellulose (CMC-Na) with superabsorbent and water-holding capability. With a high mobility of ions in the three dimensional porous network provided, the gel electrolyte obtained exhibits a satisfactory conductivity compared to common liquid polysulfide electrolytes. Through the strong coordination between carboxylate groups on CMC-Na polymer chains and metal ions of the photoanode surface, the gel electrolyte prepared also shows good contact with the surfaces of mesoporous photoanodes. As a result, an impressive PCE of 9.21%, among the highest efficiency of quasi-solid-state and solid-state QDSCs reported, was obtained for gel electrolyte based QDSCs with CdSeTe as the photosensitizer and Cu2 S as the counter electrode. Furthermore, the stability of the resultant QDSC device is improved significantly.